Do Fome Zero ao Bolsa Família: os embates intragovermantais ma transformação do programa em política pública - Barboza, Victor Hugo (Universidade Federal de São Carlos, 2019)
The present research proposes to analyze how the transformation of the main pre-election government program, the Programa Fome Zero, to the Programa Bolsa Família occurred. The proposed analysis seeks to contribute to the literature of public policies and presidential choices through a specific program and how the change of this policy occurred due to clashes within the Workers Party and in the ministerial spheres in a debate between the events occurred with the main theories of public policies of authors such as Kingdon (2003), Hall (1993), Campbell (2002), and Sabatier & Hank Jenkins – Smith (1999). Such research, where there was a migration from one public policy to another, it was necessary to seek the intragovernmental factors and the formations of different coalitions within the Workers Party in the power struggle for a public policy and also to analyze the preferences of President Lula, trying to understand how he acted before, during and after the process of transforming the Programa Fome Zero into the Programa Bolsa Família.
From Fome Zero to Bolsa Família: intragovernmental clashes in the transformation of the program into public policy
Keywords: Programa Fome Zero; Programa Bolsa Família; Segurança alimentar; Coalizões intrapartidárias; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS